U.S. oil company stock returns and currency fluctuations - Mollick, Andre; Nguyen, Khoa H (Managerial Finance, 2015)
Purpose The purpose of this is paper is to pay a closer look at the 2008-2009 financial crisis (and its aftermath) and analyzes stock returns of nine major US oil companies as well as the oil and gas sector under daily data from January 1992 to April 2012. Design/methodology/approach The authors adopt the arbitrage pricing theory model to examine the relationship between stock returns and their influences including oil price return, yield spreads, and US dollar index return. The authors also provide a test for structural changes in each regression model of return series to capture for multiple breaks. To examine the asymmetric effect of oil price returns on stock returns, the authors separate oil price returns series into two series: positive changes in oil price and negative changes in oil price. Findings The authors find stock returns of oil companies as well as the oil and gas sector are positively affected by oil prices and have stronger effects in the downward direction. Interestingly, The authors find the effects of oil price movements on stock returns increase over time. The authors examine the possibility that investors wishing to hedge against a weakening USD invest in US oil companies and find that more than half of these companies benefit from a weaker USD against the JPY, while all strongly benefit from a weaker USD against major currencies. Originality/value The authors employ daily data for two-decade period including the last global financial crisis. Due to the long-term period covered in this study, sequential Bai-Perron tests are used to detect structural breaks of stock return series. In addition, the data-dependent procedures result in good specifications throughout with white-noise processes in almost all cases.
Keywords: Exchange rates; Oil companies; Oil prices; Stock returns; USA; dept.fin

Dynamic responses and tail-dependence among commodities, the US real interest rate and the dollar - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (Empirical Economics, 2017)
Keywords: dept.fin

U.S. stock markets and the role of real interest rates - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (The Quarterly Review of Economics and Finance, 2016)
Using weekly data from January 3, 2003 to March 27, 2015, we examine the responses of U.S. stock returns (S&P 500, DJIA, and NASDAQ) to monetary policy, controlling for WTI oil prices and the value of the U.S. dollar (USD) against major currencies. Based on differences between the federal funds rate and inflation expectations, U.S. real interest rates have become continuously negative since January 28, 2009. Vector auto-regressions (VARs) suggest stronger linkages more recently and vine copula models identify the structure of dependence across these markets, which can help investors optimize portfolio diversification.
Keywords: Exchange rates; Oil prices; Real interest rates; U.S. stock markets; Vine copulas; dept.fin